VALUASI EKONOMI EKOSISTEM TERUMBU KARANG WAKATOBI - Ahmad Mansyur; Sjamsu Alam Lawelle (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
Wakatobi marine waters is a conservation area by the Minister of Forestry No. 393/Kpts-VI/1996 and as supporting public welfare Wakatobi based on Law No. 29/2003, concerning the establishment of Wakatobi. Under these conditions, require utilization towards the harmony between the two conditions. This can be realized through the efforts of the economics benefit assessment of marine protected areas (MPA) based on the direct benefits, indirect benefits, benefits of choice and the benefits of the existence and benefits of coral reef ecosystems heritage. Referred embodiment can be achieved through a change in revenue, lost revenue, cost vacant, preventive cost, cost property, wage differences, travel expenses, proxy against the market price, replacement cost and contingent approach. All that in the application to assessment of direct benefits, indirect benefits, benefits of choice and the benefits of the existence and benefits of coral reef ecosystems heritage. As a result, that the economic benefits of the Wakatobi MPA every year in one hectare obtained around Rp45,785,447,753 (direct benefits), Rp14,883,987,561 (indirect benefits), Rp9,157,089,551 (benefit option), Rp2,155,107,303 (benefit existence) and Rp4,031,174,791 as the benefits of heritage, When associated with a total area of Wakatobi MPA (582.15 Ha), the obtained total constribution MPA to Wakatobi GDP Rp44,244,838,791,317 annually. Finally, it can be encouraged that with the consequent loss a nominal value due to damage of MPA, it is expected to all stakeholde utilize natural resources more effectively, efficiently, sustainably and reducing anthropogenic activities that are destructive.Keywords: Marine Protected Areas, The Economic Benefits, The GDP Wakatobi